Alpiniae oxyphyllae fructus possesses neuroprotective effects on H2O2 stimulated PC12 cells via regulation of the PI3K/Akt signaling Pathway - Li, Ruolan; Wang, Lingyu; Zhang, Qing; Duan, Huxinyue; Qian, Die; Yang, Fei; Xia, Jun (Frontiers in Pharmacology, 2022)
Backgroud: Alzheimer's disease (AD) is a typical neurodegenerative disease, which occurs in the elderly population. Alpiniae oxyphyllae Fructus (AOF) is a traditional Chinese medicine that has potential therapeutic effect on AD, but the mechanism behind it is unclear. Methods: Firstly, the main chemical components of AOF were identified by LC-MS, while the main active ingredients and targets were screened by TCMSP database. At the same time, AD-related target proteins were obtained using Genecards and OMIM databases. PPI was constructed by cross-linking AOF and AD targets, and GO enrichment analysis and KEGG pathway enrichment analysis were performed to identify the relevant biological processes and signaling pathways. Finally, based on the H2O2-stimulated PC12 cell, flow cytometry, WB and immunofluorescence experiments were performed to verify the protective effect of AOF on AD. Results: We identified 38 active ingredients with 662 non-repetitive targets in AOF, of which 49 were potential therapeutic AD targets of AOF. According to the GO and KEGG analysis, these potential targets are mainly related to oxidative stress and apoptosis. The role of AOF in the treatment of AD is mainly related to the PI3K/AKT signaling pathway. Protocatechuic acid and nootkatone might be the main active ingredients of AOF. In subsequent experiments, the results of CCK-8 showed that AOF mitigated PC12 cell damage induced by H2O2. Kits, flow cytometry, and laser confocal microscopy indicated that AOF could decrease ROS and increase the activity of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px), while AOF could also increase mitochondrial membrane potential (MMP), thereby inhibiting apoptosis. Finally, immunofluorescence and WB results showed that AOF inhibited the expression of BAX and caspase-3 in PC12 cells, and promoted the expression of Bcl-2. At the same time, the phosphorylation levels of PI3K and Akt proteins were also significantly increased. Conclusion: This study suggests that AOF had the potential to treat AD by suppressing apoptosis induced by oxidative stress via the PI3K/Akt pathway. Keywords: Alzheimer's disease, Alpiniae oxyphyllae Fructus, network analysis, apoptosis, PI3K, Akt